Dam removal blind spots: debating the importance of community engagement in dam decommissioning projects - Matanzima, Joshua; Mosuoe-Tsietsi, Teboho (Frontiers in Water, 2023)
This article calls for social justice within the transition from dam building to decommissioning. Dam decommissioning is escalating in the global north, and sooner than later, the tied will spread to the global south. Though dam removal is an essential strategy for riverine landscape restoration, it may yield negative social outcomes for communities living along dams. Ecological restoration must not be achieved at the expense of local communities. Decisions on dam removal are predominantly made by experts and government agencies, often to the exclusion of local communities. For this reason, the decisions to remove several dams in the global north have been opposed by local communities leading to suspension or, in worst-case scenarios, reversal of such decisions. By referring to cases from Europe, USA, and Canada where dam removals have been opposed, this article argues for better incorporation of local communities in decision-making. Community consultations and consent are key in achieving successful decommissioning with minimal harm on communities. Yet, they have not received sufficient attention in dam removal conversations. The socio-economic issues are also not sufficiently interrogated in the literature on dam removal. We underscore this gap and provides recommendations for best social performance in dam removals.